Peningkatan Kualitas Pembelajaran Sekolah Melalui Pelatihan Penggunaan Media Pembelajaran Interaktif - Moh Halim; Riyanto Setiawan Suharsono; Rusdiyanto Rusdiyanto (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
This community service was carried out to enhance the capacity of teachers at SMP Muhammadiyah 11 Wuluhan Jember in developing learning devices integrated with literacy, Character Education Strengthening (PPK), and Higher Order Thinking Skills (HOTS). This activity is important because some teachers have not fully mastered the concept of learning devices that combine technology and character, resulting in less meaningful teaching and low student engagement. The implementation method involved a two-day interactive workshop, including material presentation, group discussions, practice in preparing RPP based on interactive media, and evaluation through pre-tests and post-tests. The results showed a post-test score improvement of up to 35%, more creative and innovative RPP quality, and teachers’ positive attitudes toward learning technology. Program sustainability is supported through the establishment of a technology assistance team and plans for follow-up training. These findings confirm that systematic interventions can enhance teacher competence, promote creative learning, and strengthen the 21st-century education ecosystem sustainably.